2003
DOI: 10.1044/1058-0360(2003/087)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voicing and Syntactic Complexity on Sign Expression in Adductor Spasmodic Dysphonia

Abstract: Clients with adductor spasmodic dysphonia (ADSD) tend to exhibit inter- and intraclient variability of signs and symptoms. This variability may result in inaccurate assessment of severity. Accurate assessment of severity requires knowledge concerning the factors that affect the expression of ADSD signs and symptoms. This study examined ADSD sign expression as a function of voicing and syntactic complexity. Fifteen ADSD participants and 15 control participants completed a task consisting of 30 sentences. ADSD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Our results replicate Erickson's [7] report of greater sign expression in ADSD during voiced consonants as compared to voiceless consonants and confirm task specificity as a feature of ADSD that potentially distinguishes it from MTD. Erickson [7] attempted to explain increased sign expression during voiced phonemes in ADSD as reflecting an underlying movement control disorder that affects vocal fold adduction for phonation onset.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our results replicate Erickson's [7] report of greater sign expression in ADSD during voiced consonants as compared to voiceless consonants and confirm task specificity as a feature of ADSD that potentially distinguishes it from MTD. Erickson [7] attempted to explain increased sign expression during voiced phonemes in ADSD as reflecting an underlying movement control disorder that affects vocal fold adduction for phonation onset.…”
Section: Discussionsupporting
confidence: 80%
“…Our results replicate Erickson's [7] report of greater sign expression in ADSD during voiced consonants as compared to voiceless consonants and confirm task specificity as a feature of ADSD that potentially distinguishes it from MTD. Erickson [7] attempted to explain increased sign expression during voiced phonemes in ADSD as reflecting an underlying movement control disorder that affects vocal fold adduction for phonation onset. Erickson [7] reasoned that speech tasks that require rapid laryngeal adjustment should be most impaired, and suggested that more ADSD signs should occur following voiced plosives, because the The percentage of subjects meeting the cutoff criterion for each disorder group was calculated by subtracting an individual participant's mean severity rating for the voiceless sentence from their mean severity rating for the voiced sentence.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations